Scoping review of maternal and newborn health interventions and programmes in Nigeria. Issue 2 (15th February 2022) - Nasir, Naima; Aderoba, Adeniyi Kolade; Ariana, Proochista
Abstract : Objective: To systematically scope and map research regarding interventions, programmes or strategies to improve maternal and newborn health (MNH) in Nigeria. Design: Scoping review. Data sources and eligibility criteria: Systematic searches were conducted from 1 June to 22 July 2020 in PubMed, Embase, Scopus, together with a search of the grey literature. Publications presenting interventions and programmes to improve maternal or newborn health or both in Nigeria were included. Data extraction and analysis: The data extracted included source and year of publication, geographical setting, study design, target population(s), type of intervention/programme, reported outcomes and any reported facilitators or barriers. Data analysis involved descriptive numerical summaries and qualitative content analysis. We summarised the evidence using a framework combining WHO recommendations for MNH, the continuum of care and the social determinants of health frameworks to identify gaps where further research and action may be needed. Results: A total of 80 publications were included in this review. Most interventions (71%) were aligned with WHO recommendations, and half (n=40) targeted the pregnancy and childbirth stages of the continuum of care. Most of the programmes (n=74) examined the intermediate social determinants of maternal health related to health system factors within health facilities, with only a few interventions aimed at structural social determinants. An integrated approach to implementation and funding constraints were among factors reported as facilitators and barriers, respectively. Conclusion: Using an integrated framework, we found most MNH interventions in Nigeria were aligned with the WHO recommendations and focused on the intermediate social determinants of health within health facilities. We determined a paucity of research on interventions targeting the structural social determinants and community-based approaches, and limited attention to pre-pregnancy interventions. To accelerate progress towards the sustainable development goal MNH targets, greater focus on implementing interventions and measuring context-specific challenges beyond the health facility is required.